Advancing Entrepreneurship in the United Arab Emirates Start-up Challenges and Opportunities - Minhas, Wasif A. (Springer International Publishing, 2018)
Reflecting increasing investment in entrepreneurship in the United Arab Emirates (UAE), this new book offers extensive coverage of the factors that enable Emiratis to start and grow a business. Exploring the challenges faced by local start-ups, this book provides insight into the way that entrepreneurship is both perceived and governed in the UAE and how this differs to other countries. The author builds on rich empirical research to propose a model of entrepreneurship which is specific to the UAE, taking into account the role of culture, family and government support. This innovative book underlines the importance of human behaviour in creating successful Emirati start-ups and business opportunities. .